Sick Human Entity - Delgado, Honorio (1960)
Maximum is highest privilege and responsibility of the medical profession to serve the ailing man according to their complexity of a biological, social and spiritual. To accomplish this task it is necessary to cultivate diverse and difficult scientific disciplines and to apply to art, to the time you put into play the resources of exquisite treatment and psychological insight. It does to the extent that their vocation is authentic, competence is based on actual knowledge and is illuminated by a higher conception of human nature. Hence since Hippocrates, writing in his famous Law, understand medicine, if exercised with love, as a sacred thing, it should only be to impart sacred persons, that is, worthy of respect and veneration.